Plant Virus Nanoparticles for Anti-cancer Therapy - Venkataraman, Srividhya; Apka, Paul; Shoeb, Erum; Badar, Uzma; Hefferon, Kathleen (Frontiers in Bioengineering and Biotechnology, 2021)
Plant virus nanoparticles (VNPs) are inexpensive to produce, safe, biodegradable and efficacious as treatments. The applications of plant virus nanoparticles range from epitope carriers for vaccines to agents in cancer immunotherapy. Both VNPs and virus-like particles (VLPs) are highly immunogenic and are readily phagocytosed by antigen presenting cells (APCs), which in turn elicit antigen processing and display of pathogenic epitopes on their surfaces. Since the VLPs are composed of multiple copies of their respective capsid proteins, they present repetitive multivalent scaffolds which aid in antigen presentation. Therefore, the VLPs prove to be highly suitable platforms for delivery and presentation of antigenic epitopes, resulting in induction of more robust immune response compared to those of their soluble counterparts. Since the tumor microenvironment poses the challenge of self-antigen tolerance, VLPs are preferrable platforms for delivery and display of self-antigens as well as otherwise weakly immunogenic antigens. These properties, in addition to their diminutive size, enable the VLPs to deliver vaccines to the draining lymph nodes in addition to promoting APC interactions. Furthermore, many plant viral VLPs possess inherent adjuvant properties dispensing with the requirement of additional adjuvants to stimulate immune activity. Some of the highly immunogenic VLPs elicit innate immune activity, which in turn instigate adaptive immunity in tumor micro-environments. Plant viral VLPs are nontoxic, inherently stable, and capable of being mass-produced as well as being modified with antigens and drugs, therefore providing an attractive option for eliciting anti-tumor immunity. The following review explores the use of plant viruses as epitope carrying nanoparticles and as a novel tools in cancer immunotherapy.